Light-activatable manganese carbonate nanocubes elicit robust immunotherapy by amplifying endoplasmic reticulum stress-meditated pyroptotic cell death - Chuan Wu; Mingquan Gao; Weidong Xiao; Xie Huang; Xinrui Yang; Zifei Wu; Xudong Yu; Banghui Mo; Zaizhi Du; Ziqian Shang; Jing Liu; Can Shi; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Although tumor immunotherapy has emerged as a promising treatment modality, it faces significant challenges stemming from the immunosuppressive characteristics of the tumor microenvironment (TME), the low immunogenicity of tumors, and the poor specificity of immunoactivation. These factors can hinder the efficacy of immunotherapeutic approaches and lead to immune-related adverse events. This study reports a multifunctional nanocube (Mn-ER-Cy) that integrates Mn carbonate (MnCO3) and a photosensitizer (ER-Cy) by targeting tumor-cell endoplasmic reticulum (ER). The results demonstrate that Mn-ER-Cy preferentially accumulates in tumor tissues and is retained within ER organelles, facilitating photothermal therapy (PTT) and photodynamic therapy (PDT) upon exposure to 808 nm light irradiation. Triggered by acidic TME and light irradiation, MnCO3 is rapidly degraded to Mn2+, which in turn promotes the generation of reactive oxygen species through the Mn2+-mimic Fenton reaction, enabling chemical dynamics therapy (CDT). Triple-modal synergistic therapy simultaneously happens in ER to induce excessive ER stress, which subsequently amplify highly immunogenic pyroptotic cell death through activating NLRP3 inflammasome, caspase-1, and gasdermin D (GSDMD) pathway. Meanwhile, the decomposition of MnCO3 consumes H+ and contributes to an increased intracellular pH by regulating lactic acid levels, thereby counteracting the immunosuppressive acidic TME. Furthermore, Mn-ER-Cy serves as an inherent dual-modality imaging contrast agent for near-infrared fluorescence and photoacoustic imaging, facilitating imaging-guided precision therapy. These findings underscore the potential of Mn-ER-Cy to substantially enhance the efficacy and specificity of tumor immunotherapy, portraying a bright prospect to improve the clinical outcomes of patients with cancer.